PREDICTIVE VALUE OF SERUM INTERLEUKIN 31 IN DIAGNOSIS OF OSTEOPOROSIS IN POSTMENOPAUSAL WOMAN: A NOVEL CASE–CONTROL STUDY FROM IRAQ - Ghalib Abid, Asma; Salman Al-hadithi, Hayfaa; Gorial, Faiq I (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study was to assess the predictive value of serum level of interleukin 31 (IL31) in diagnosis of osteoporosis (OP) in postmenopausal women. Methods: This case–control study was conducted on 80 individuals, 50 of them with postmenopausal OP diagnosed using dual X-ray absorptiometry study, and the other 30 were healthy postmenopausal female controls. Serum level of IL31 was measured using enzyme-linked immunosorbent assay technique in both groups. Results: The mean age of patients was 65.3±4.8 years and controls was 61.1±3.9 years. Mean serum IL31 level was significantly higher among postmenopausal patients with OP compared to healthy controls (83.5±34.2 vs. 34.9±7.3ng/ml, p<0.05). The optimum cutoff value of serum IL31 that can differentiate between patients with OP in postmenopausal women from controls was >44.51 ng/ml with perfect positive predictive value (PPV) (100%), very high accuracy of 92.5%, 88% sensitivity, 100% specificity, and negative predictive value (NPV) 83.3%. Conclusions: Serum IL31 level was significantly higher in postmenopausal osteoporotic women compared to healthy controls. It was a valid measure with high accuracy and perfect PPV and specificity, high sensitivity, and NPV. It can be used to confirm the diagnosis of OP in postmenopausal women.